EXPLORING FINTECH LENDING USAGE IN INDONESIA THROUGH A SOCIO-CULTURAL AND PSYCHOLOGICAL PERSPECTIVE - Magfiratul Fitria; Afandinata Ariawan; Zevanya Angelia; Ananta Yudiarso (UNIVERSITAS SEBELAS MARET (UNS), 2025)
The rapid expansion of fintech lending in Indonesia has coincided with rising concerns over digital debt dependency, particularly among low-income and young populations. While regulatory and financial risks have dominated public discourse, less attention has been paid to the psychosocial and socio-cultural conditions underlying fintech lending behavior. This study examines the deviant aspects of fintech use through an integrated psychosocial-cultural lens, highlighting how such behaviors arise not solely from individual irresponsibility but from the intersection of emotional vulnerability, social marginalization, and the cultural normalisation of debt. A mixed-methods approach was employed. The first phase involved a scoping literature review to identify conceptual and theoretical gaps. The second phase applied supervised machine learning (SVM, Decision Tree, Random Forest, Neural Network) to national survey data (BPS and OJK) to detect behavioral patterns. The third phase conducted a thematic analysis of in-depth interviews with five fintech users from high-risk urban areas. The findings indicate consistent patterns of emotional fragility, fintech use dependency, institutional distrust, and symbolic adaptation to debt culture. These behaviors reflect structural and psychological deviance, where fintech use serves as both a coping strategy and a socio-cultural adaptation amid economic precarity and institutional exclusion. This study contributes to interdisciplinary scholarship by extending strain and labeling theories in tandem with psychological theories of vulnerability and coping, reframing fintech use as a socially and emotionally constructed adaptation rather than moral failure. Policy-wise, it calls for culturally grounded financial literacy, stronger digital consumer protection, and inclusive reforms that address systemic inequality and distrust in formal institutions